ICSID 2017 Annual Report - International Centre for Settlement of Investment Disputes (Washington, DC, 2017)
Today, ICSID is the acknowledged world leader in investor-State dispute settlement. It has administered more than 70% of all known international investment proceedings. Over the past year alone, ICSID administered 258 cases, the most in any single year of its history. These cases are administered in every region of the world, and are decided by a diverse international group of specialist arbitrators, conciliators and ad hoc committee members. ICSID’s case administration is complemented by its leading role in training parties about international investment dispute settlement and in publishing cutting-edge legal scholarship on developments in the field. This systemic perspective enhances ICSID’s ability not only to provide the most effective administrative service, but also to envision and implement continuous improvement of investment dispute settlement.